Analisis Gaya Komunikasi Populis Prabowo Subianto dalam Kampanye Pemilihan Presiden 2024 - Fridolin Edwin Moke; Salvatore Simarmata (Jurnal InterAct, 2025)
Populism has become popular around the world and in Indonesia in the last decade. Populism as a communication style dominated during the 2024 presidential election campaign. One of the candidates, Prabowo Subianto on various occasions often exercised a populist communication style. The purpose of this research is to analyze the populist communication style of Prabowo Subianto in the 2024 presidential election. The theories used in this research are political communication theory, digital media, election campaign, populist communication, populism, and populist communication style. The method in this research is content analysis of Prabowo Subianto's direct statements as reported by kompas.com and detik.com using a quantitative approach. The results showed that Prabowo Subianto's populist communication style in the 2024 presidential election was dominated by hostile behaviour using facts or events to polarize public opinion, provoking positive emotions by showing enthusiasm, hope and pride, simplifying complex problems, as well as charismatic leadership by displaying charismatic traits and positioning himself as the saviour of the nation. This study highlights the continuing significance of populist discourse in shaping electoral strategies and public perception in Indonesian democracy.